312 Predictors of work participation of young adults with mild intellectual disabilities. (11th October 2013) - Holwerda, A; Klink, van der; Boer, de; Groothoff,; Brouwer,
Abstract : Objectives: Unemployment rates among individuals with Intellectual Disabilities (ID) are three to four times higher compared to their non-disabled peers. Evidence for factors associated with work participation of individuals with ID stems from a limited number of cross-sectional studies. Furthermore, studies on predictors for sustainable work participation among young adolescents with ID are lacking altogether. Therefore, the aim of this study was to investigate which factors predict work participation, finding work as well as sustainable employment, of young adults with mild intellectual disabilities. Methods: We obtained data on 735 individuals with mild ID, aged 15–27 years, applying for a disability benefit at the Dutch Social Security Institute. Participants completed a questionnaire on personal and social factors at baseline, which were linked to registry-data regarding work outcome. The follow-up period ranged from one year and three months to two years and nine months. Cox regression (survival) analyses were conducted in order to examine which factors predicted work participation. Results: Living situation, expectation regarding future work level and self-esteem all predicted finding work as well as sustainable employment for at least 6 months for individuals with mild intellectual disabilities. Motivation was only related to finding work. Conclusion: Personal and social factors are valuable in predicting finding work as well as sustainable employment. As this study is the first prognostic study to our knowledge to assess the predictive value of personal and social factors related to work outcome in this group, further research is needed to establish the predictive value of the factors found.